Are World Leaders Loss Averse? - Matthew Gould; Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2019)
We focus on the preferences of an extremely salient group of highly-experienced individuals who are entrusted with making decisions that affect the lives of millions of their citizens, heads of government. We test for the presence of a fundamental behavioral bias, loss aversion, in the way heads of government choose decision rules for international organizations. If loss aversion disappears with experience and high-stakes it should not exhibited in this context. Loss averse leaders choose decision rules that oversupply negative (blocking) power at the expense of positive power (to initiate affirmative action), causing welfare losses through harmful policy persistence and reform deadlocks. We find evidence of significant loss aversion (λ = 4:4) in the Qualified Majority rule in the Treaty of Lisbon, when understood as a Nash bargaining outcome. World leaders may be more loss averse than the populous they represent.
Keywords: D03; D81; D72; C78; 330; loss aversion; behavioral biases; constitutional design; voting; bargaining; voting power; EU Council of Ministers